Dual-wavelength image-plane digital holography for dynamic measurement - Hennelly, Bryan M. (2010)
A dual-wavelength image-plane digital holography, combined with a windowed Fourier analysis, is presented for dynamic measurement of a vibrating object. In order to expand the range of the velocity measurement, the object is simultaneously illuminated by two lasers with different wavelengths. A sequence of digital holograms of a vibrating object is captured by a CCD camera and two wrapped phase maps are retrieved from each digital hologram. At each instant, a new phase distribution with a synthetic wavelength is obtained by subtracting these two wrapped phase maps. A windowed Fourier analysis is then applied spatially and temporally to retrieve the high-precision displacement and velocity of the tested object. Experimental results show the requirement on the camera capture frequency is reduced by the proposed method.